Effects of storytelling to facilitate EFL speaking using Web-based multimedia system. Issue 2 (17th February 2016) - Hwang, Wu-Yuin; Shadiev, Rustam; Hsu, Jung-Lung; Huang, Yueh-Min; Hsu, Guo-Liang; Lin, Yi-Chun
Abstract : This study applied storytelling in the English as a foreign language (EFL) classroom in order to promote speaking skills. Students were asked to practice speaking EFL through producing individual and interactive stories with a Web-based multimedia system. We aimed to investigate an effectiveness of applying individual and interactive storytelling on speaking skills and the potential effects of multimedia aids in storytelling to facilitate language learning. Furthermore, we explored the relationships between research variables of this study, such as speaking performance on individual and interactive storytelling, the number of animation representations, and the system actual usage, with learning achievement. Four main findings were found in this study. First, students who used the system for creating stories significantly outperformed students who did not use it on the post-test. This finding suggests that storytelling activity with support of the system was beneficial for improving speaking skills. Second, speaking performance and the number of animation representations significantly correlated with learning achievement. Students who performed well during learning activities usually studied diligently and scored higher on final test. Animations could help students remember vocabulary and practice speaking to describe their animated stories. Third, only the speaking performance on individual storytelling was found as the significant predictor of learning achievement. Students working individually on storytelling were independent; they were less distracted from others, and had more opportunity for practice. The last but not the least, most students expressed positive perceptions and attitude toward the system and learning activities. Based on these findings, we suggest that storytelling learning activities supported by the Web-based multimedia system and implementing them in EFL learning classroom can be beneficial for facilitating speaking skills. Students can remember new vocabulary better, practice speaking skills more frequently, become competent in speaking target language, and improve learning performance.